IMPLEMENTASI STRATEGI PEMBELAJARAN DISCOVERY LEARNINGDALAM MENINGKATKAN KETERAMPILANBERFIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA MUHAMAMDIYAH 2 SANGKAPURA - Junaina Bintang Novita; Asrori Asrori; Rusman Rusman (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
The application of discovery learning strategies in improving critical thinking skills at SMA Muhammadiyah 2 Singapura is the title as well as the goal of this research. This study uses research methods with a qualitative approach or type of descriptive research. The results of the research implementation of discovery learning strategies in improving students' critical thinking skills in Islamic religious education subjects went very well, this was seen from the results of observations and learning activities where students experienced an increase in critical thinking when using discovery learning strategies to get a percentage 85% with good category. Critical thinking skills in students are also good. The supporting factors of this research start from the curiosity of students, self-confidence, opportunity and time, and learning selection strategies. While the inhibiting factor is the opposite of the supporting factor, namely the lack of curiosity of students, fear, and inferiority.